Developing narrative theory : life histories and personal representation - Goodson, Ivor (Routledge, 2013)
"We live in an age of narrative: life stories are a crucial ingredient in what makes us human and, in turn, what kind of human they make us. In recent years, narrative analysis has grown in interest and use across many areas of research; up until now, however, this rapidly developing approach has lacked the firm theoretical underpinning that would allow researchers to both approach such research in a reliably structured way, and to interpret the results more effectively. Developing Narrative Theory looks at the contemporary need to study life narratives, considers the emergence and salience of life narratives in contemporary culture, and discusses different forms of narrativity. It shows in detail how life story interviews are conducted, and demonstrates how the process often begins with relatively unstructured life story collection but moves to a more collaborative exchange, where sociological themes and historical patterns are scrutinised and mutually explored. At the core of this book, the author shows that, far from there being a singular form of narrative or an infinite range of unique and idiosyncratic narratives, there are in fact clusters of narrativity and particular types of narrative style. These can be grouped into four main areas: Focussed Elaborators; Scripted Describers; Armchair Elaborators; and Focussed Describers. Drawing on data from several large-scale studies from countries across the world, Professor Goodson details how theories of narrativity and life story analysis can combine to inform learning potential. Timely and innovative, this book will be of use to anyone researching or developing learning strategies and resources, as well as those interested in lifelong learning and professional and self-development practices"